Thermal studies on recycled aggregate concrete modified with carbonated and bio-deposited recycled aggregates - Sivamani, Jagan; Periasamy, Thiyaneswaran (Engineering and Applied Science Research, 2023)
Several research studies have been conducted to investigate the hardened and durability characteristics of the normal aggregate concrete (NAC) and recycled aggregate concrete (RAC). Similarly, few studies have been done to examine the thermal behaviour of the NAC and RAC. However, the influence of elevated temperature on the RAC with treated recycled coarse aggregate (RCA) in the concrete still needs to be investigated. This study presents the comparative discussion on the thermal performance of NAC, RAC, carbonated recycled aggregate concrete (CRAC) and bio-deposited recycled aggregate concrete (BRAC) at various elevated temperatures of 25, 200, 500 and 800°C. The investigation involves the determination of residual compressive strength, tensile strength, elastic modulus and thermal conductivity with a series of concrete mixtures under elevated temperatures. The optimal residual strength was observed at 500°C, beyond exposure of it causes a reduction in the strength. The residual strength of NAC, RAC, CRAC and BRAC at optimal temperature was reduced by 30.10%, 7.06%, and 31.02%. The equivalence of the thermal expansion coefficient of RCA with cement paste improves the residual response of RAC, and higher porosity of RCA decreases the thermal conductivity of the RAC by 43.06% compared to control concrete. Furthermore, no concrete samples crumbled at 800°C, but the residual properties tend to decrease for all mixes.